“Keep On Trying”: A Narrative Inquiry of Indonesian Vocational Students on Resilience Post the COVID-19 Pandemic - Christiana Sidupa (Bina Nusantara University, 2023)
The research aimed to find out what Indonesian vocational students’ constructions of resilience in relation to academic achievement and improvement of English writing skills post the COVID-19 pandemic. A narrative inquiry method was adopted in order to make sense of the unique and common vocational students’ experiences. Specifically, narrative inquiry informed the whole research process by focusing on three aspects of the research process: data collection, data transcription, and data analysis. Excerpts from semi-structured and focus group interviews with 11 participants from three provinces on Java Island were analyzed. Research results indicate that academic resilience is reinforced by personal qualities, such as the capacity to keep trying, the ability to handle hard circumstances, and self-discipline. It also reveals that teachers’ support, students’ hope and optimism appear to play a protective role in assisting the students to cope with available English writing challenges. Finally, the research concludes with pedagogical implications, mainly for vocational school teachers.